Evaluation of coral reef condition in Nogas Island, Philippines using multiple benthic indicators - Gonzales, Marvin B. (Miagao, Iloilo University of the Philippines Visayas, 2021)
Worldwide coral reefs are rapidly declining because of numerous stressors such as climate change-related bleaching and frequent storm damage, predation, and other anthropogenic disturbances such as pollution and overfishing. Benthic foraminifera are used as a powerful tool for environmental assessment because they are extremely sensitive to both physical and chemical variations in the environment. In this study, benthic foraminifera and multiple benthic indices were utilized to determine and assess the status and viability of the reef environment in Nogas Island, Antique. Coral Condition Index (CCI) revealed that corals were marginal between healthy and damaged conditions, with low coral cover and diversity, and prevalence of recently dead corals. The majority of the reef sediment constitutent was unidentifiable grains, followed by coral fragments, symbiont-bearing foraminifera or mollucs debris, SEDCON Index (SI) showed that autotrophy and heterotrophy were principally controlling the sediment community structure, seconded by symbiotic calcification and physical erosion. The functional group of large symbiont-bearing foraminifera dominated the assemblage with a relative abundance of 94.75 %, followed by small and heterotrophic taxa (4.0%), then opportunities taxa (1.25%).The assemblages were consistently dominated by Family Calcarinidae, whose abundance represented about 76.8% of the total assemblage, followed by Genus Amphistegina and Heterostegina depressa with 8% and 3.5%, respectively. FoRAM Index (FI) values were very high (FI>4.0), which implied that the present environment was suitable for the growth of calcifying mixotrophs and could support recovery after significant mass mortality events. The Foram Stress Index (FSI) revealed that the sedimentary habitat was high quality and unpolluted/prisstine (FSI>9.0). The findings of this study provided an effective bioindicator for the assessment of the reef condition of the island.
Thesis (M.S. Ocean Sciences) -- Miagao, Iloilo : University of the Philippines Visayas, August 2021.
Keywords: Coral reef -- Nogas Island, Philippines